The complete works - Fuller, Andrew 1754-1815 (De Gruyter, 2021)
When Socinianism was at the height of its power, Andrew Fuller challenged it in its self-professed point of greatest strength --the virtue encouraged by its principles of theistic rationality. Do the extended implications of its principles compare favorably with Calvinism in the development of virtue? Using their own writings and the admissions they make concerning piety and virtue among Socinians, Fuller compared both systems in their tendency to convert profligates to a life of holiness, to convert professed unbelievers, their development of a standard of morality, to encourage love to God, candor and benevolence toward men, encourage humility and charity, promote love for Christ and veneration of Scripture, develop happiness, cheerfulness, gratitude, obedience, and heavenly-mindedness in the followers of the respective systems. If challenged that he is being judgmental and has focused on subjective criteria, Fuller replied that he is merely engaging the Socinians at the place where they have invited investigation. Fuller intended to lay bare the emptiness of the Socinian boast to virtue. The work first was published in 1793